Bacillus spp. as potential probiotics: promoting piglet growth by improving intestinal health - Tang, Xiaopeng; Zeng, Yan; Xiong, Kangning; Zhong, Jinfeng (Frontiers in Veterinary Science, 2024)
The application of Bacillus spp. as probiotics in the swine industry, particularly for piglet production, has garnered significant attention in recent years. This review aimed to summarized the role and mechanisms of Bacillus spp. in promoting growth and maintaining gut health in piglets. Bacillus spp. can enhance intestinal barrier function by promoting the proliferation and repair of intestinal epithelial cells and increasing mucosal barrier integrity, thereby reducing the risk of pathogenic microbial invasion. Additionally, Bacillus spp. can activate the intestinal immune system of piglets, thereby enhancing the body’s resistance to diseases. Moreover, Bacillus spp. can optimize the gut microbial community structure, enhance the activity of beneficial bacteria such as Lactobacillus, and inhibit the growth of harmful bacteria such as Escherichia coli, ultimately promoting piglet growth performance and improving feed efficiency. Bacillus spp. has advantages as well as challenges as an animal probiotic, and safety evaluation should be conducted when using the newly isolated Bacillus spp. This review provides a scientific basis for the application of Bacillus spp. in modern piglet production, highlighting their potential in improving the efficiency of livestock production and animal welfare.